2001
DOI: 10.1038/sj.jim.7000108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical factors on the production of bacteriocin from Pediococcus acidilactici ITV 26

Abstract: The effect of pH, temperature and agitation on growth and bacteriocin production by Pediococcus acidilactici ITV 126 was investigated. Experiments were made in flasks containing MRS medium at 30 to 40 degrees C, pH 5 to 7 and agitation 0 to 200 rpm. Factor levels were arranged in a 2(3) factorial design with central and axial points. Anova and Tukey paired comparison tests showed that a temperature of 35 degrees C favored bacteriocin production, whereas 40 degrees C was best for cell growth. A statistical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…the results from the present study also showed that the production of bacteriocin was not influenced by agitation. this is in accordance with the study by caldeón-Santoyo et al (5) who reported that agitation did not affect the production of bacteriocin.…”
Section: Resultssupporting
confidence: 82%
“…the results from the present study also showed that the production of bacteriocin was not influenced by agitation. this is in accordance with the study by caldeón-Santoyo et al (5) who reported that agitation did not affect the production of bacteriocin.…”
Section: Resultssupporting
confidence: 82%
“…acidification and growth. Maximum specific production has been registered mostly in the pH range 4.5e5.5, coinciding with what was reported by several authors (Calderón-Santoyo, Mendonza-García, García-Alvarado, & EscuderoAbarca, 2001;Klostermaier, Scheyhing, Ehrmann, & Vogel, 1999;Krier, Revol-Junelles, & Germain, 1998).…”
Section: Influence Of Nacl Concentration On Enterocin Productionsupporting
confidence: 84%
“…lactis. Growth optimisation studies have been conducted on pediocin AcH (BISWAS et al 1991), pediocin PD-1 (NEL et al 2001), bacteriocins produced by Pediococcus acidilactici ITV26 (CALDERON-SANTOYO et al 2001), enterocin 1146(PARENTE and HILL 1992, enterocin AS-48 (ABRIOUEL et al 2001), plantaricin ST31 (TODOROV et al 2000), plantaricin 423 (VERELLEN et al 1998), sakP (AASEN et al 2000, bacteriocins produced by Leuconostoc mesenteroides L124 and Lactobacillus curvatus L442 (MATARA- GAS et al 2003), and two bacteriocins produced by Leuconostoc mesenteroides subsp. mesenteroides FR52 (KRIER et al 1998).…”
mentioning
confidence: 99%